2016
DOI: 10.3390/jcm5110095
|View full text |Cite
|
Sign up to set email alerts
|

Do Alcohol Misuse, Service Utilisation, and Demographic Characteristics Differ between UK Veterans and Members of the General Public Attending an NHS General Hospital?

Abstract: The aim of this paper was to provide insights into alcohol misuse within UK veterans to inform as to whether their presentations differ from the general public. This was done by exploring differences in the severity of alcohol misuse between UK veterans and the general public admitted to a general NHS hospital over an 18 month period using retrospective data. All patients admitted to the hospital were screened for alcohol misuse. Those deemed as experiencing problems were referred for specialist nurse-led supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…30 It should also be noted that older veterans reported significantly more alcohol consumption than nonveterans, consistent with research in older and working-age UK personnel/veterans. 36,37 Murphy et al 38 found that compared with nonveterans, UK AF veterans referred for NHS alcohol support were more likely to be older, retired, and male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 It should also be noted that older veterans reported significantly more alcohol consumption than nonveterans, consistent with research in older and working-age UK personnel/veterans. 36,37 Murphy et al 38 found that compared with nonveterans, UK AF veterans referred for NHS alcohol support were more likely to be older, retired, and male.…”
Section: Discussionmentioning
confidence: 99%
“…31 Nonetheless, providing support appeared challenging for close companions, particularly when veterans had significant mental health difficulties. Murphy et al38 found that compared with nonveterans, UK AF veterans referred for NHS alcohol support were more likely to be older, retired, and male. At present, veteran-affiliated organizations and charities offering psychological services ensure that appropriate guidance is readily available to the carers of older veterans with dementia.…”
mentioning
confidence: 99%
“…Estimates suggest that fewer than 10% of the 15 million people in the United States with an alcohol use disorder seek professional help ; similar proportions apply to gambling addiction . Prolonged untreated addiction can cause problems for the individual and their family, and delayed treatment, often provided during a crisis, is both less effective and more costly .…”
Section: Introductionmentioning
confidence: 99%
“…Thandi et al, 2015;Iversen et al, 2007), particularly when being in periods of ' decompression' -the period of leave given to Service Personnel after deployment (Hacker-Hughes et al, 2008). However, alcohol misuse was found to continue being a problem when Service Personnel leave the UK Armed Forces, being one of the Ex-Service Personnel's most common problems for which only a small proportion of veterans seek help (Murphy et al, 2016;Alcohol-Concern, 2012;Fear, Wood & Wessely, 2009).…”
Section: Risk-drinking Behavior (Alcoholism)mentioning
confidence: 99%